Dietary emulsifier polysorbate‐80‐induced small‐intestinal vulnerability to indomethacin‐induced lesions via dysbiosis. Issue 1 (16th October 2019) - Furuhashi, Hirotaka; Higashiyama, Masaaki; Okada, Yoshikiyo; Kurihara, Chie; Wada, Akinori; Horiuchi, Kazuki; Hanawa, Yoshinori; Mizoguchi, Akinori; Nishii, Shin; Inaba, Kenichi; Sugihara, Nao; Watanabe, Chikako; et al.
Abstract: Background and Aim: Dietary emulsifiers are widely used in processed foods and officially approved as safe for intake. However, recent studies have demonstrated that some emulsifiers alter the colonic microbiota, leading to colonic low‐grade inflammation, in mice. The effect of dietary emulsifiers on small‐intestinal microbiota, which is important for gut immunity, has not been studied. We aimed to investigate the effect of a representative dietary emulsifier, polysorbate‐80 (P80), on the small‐intestinal microbiota in normal mice. Methods: Some mice were pretreated with P80 for 8 weeks with or without indomethacin administration on the last 2 days, and intestinal damage was evaluated histologically. The ileal and colonic microbiota composition was assessed using 16S rRNA polymerase chain reaction. Results: Polysorbate‐80 increased the Gammaproteobacteria abundance and decreased the α‐diversity in the small intestine. No decrease in α‐diversity was observed in the colon. P80 pretreatment exacerbated the indomethacin‐induced small‐intestinal lesions and significantly increased the interleukin‐1β expression. Culture of ileal content on deoxycholate hydrogen sulfide lactose agar showed that P80 significantly increased the colonies of the sulfide‐producing bacteria Proteus spp. (genetically identified as Proteus mirabilis ). Antibiotic pretreatment abolished the P80‐induced aggravation of indomethacin‐induced ileitis. Motility assay in semisolid agar showed that adding 0.02% P80 to the agar significantly increased the diameter of P. mirabilis colonies but not that of Escherichia coli colonies. Conclusions: Polysorbate‐80 enhances the vulnerability of the small intestine to indomethacin‐induced injury by inducing ileal dysbiosis. Direct enhancement of the motility of specific flagellated microbiota by P80 might be related to dysbiosis and intestinal injury.